The non-verbal type of small clauses in English and Lithuanian - Giparaitė, Judita (Cambridge Scholars Pub., 2010)
The study The Non-verbal Type of Small Clauses in English and Lithuanian is one of the first attempts to apply the methods of generative grammar to the analysis of a fragment of Lithuanian grammar, i.e. constructions with secondary predicates of the type.